Проклятые огнем: [роман] / Ксения Баштовая - Баштовая Ксения Николаевна (Руны любви, 2015)
Экземпляры: ф.8 (20181106) / Инвентарный номер: 58832 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445